2017
DOI: 10.1002/2017gl075317
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the energy balance in large lowland rivers, and why the bed matters

Abstract: Along many rivers, dams trap sediment and water released from the dams is clear. Downstream of the dam, temperature variability along the river is controlled by climate that warms or cools the water, the flow magnitude, and the spectral properties of water and the river's bed. Using field observations, a synoptic numerical model without calibration couples a full‐spectrum radiation balance with turbulent heat fluxes, bed conduction, and a hydraulic model that estimates depth and velocity. We show that variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Ground-surface water fluxes also influence river water temperatures due to differences in temperature between groundwater and surface water (Irvine et al, 2017). The absolute and relative contributions of these heat transfer components vary depending on factors such as climate (Cozzetto, McKnight, Nylen, & Fountain, 2006), geomorphological setting (Webb, 1995), albedo of river bed sediment (Bray, Dozier, & Dunne, 2017), shading (Johnson, 2004), wind (Story, Moore, & Macdonald, 2003) and river flow (Garner, Malcolm, Sadler, & Hannah, 2017;Webb, Clack, & Walling, 2003).…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…Ground-surface water fluxes also influence river water temperatures due to differences in temperature between groundwater and surface water (Irvine et al, 2017). The absolute and relative contributions of these heat transfer components vary depending on factors such as climate (Cozzetto, McKnight, Nylen, & Fountain, 2006), geomorphological setting (Webb, 1995), albedo of river bed sediment (Bray, Dozier, & Dunne, 2017), shading (Johnson, 2004), wind (Story, Moore, & Macdonald, 2003) and river flow (Garner, Malcolm, Sadler, & Hannah, 2017;Webb, Clack, & Walling, 2003).…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…We also assumed that the ablation zone covers 12% of the Ice Sheet as determined by Ryan et al (2019). It is safe to assume that the large majority of the energy absorbed by the sediment eventually contributes to melting of ice since less than 8% of incoming radiation that reaches the streambed is reflected away before being absorbed by a shallow water column (Bray et al, 2017) and because runoff can be retained within the Ice Sheet for 1-6 months before export (Rennermalm et al, 2013b). Thus, there is plenty of time for heat to transfer from the water to the ice.…”
Section: Impact Of Albedo Changes On Surface Meltingmentioning
confidence: 99%
“…Previous research using synoptic numerical models show that for shallow streams (0.5 m depth), 38% of the incoming spectrally integrated solar radiation is absorbed by the bed compared to 51% by the water column (Bray et al, 2017). As a result, for terrestrial streams, dark sediment along the streambed can facilitate enough energy absorption to increase water temperatures by over 2 °C (Bray et al, 2017). Isenko et al (2005) observed that this process also occurs in supraglacial streams resulting in stream temperatures up to 0.4 °C when sediment was present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dam operations have been shown to increase the connectivity between rivers and their adjoining sediments (Sawyer et al., 2009), enhancing the exchange of heat between rivers and their underlying sediments (Gerecht et al., 2011). Thus, changes to riverbed temperature may affect the energy balance of rivers in a substantive way because of the thermal coupling between the river and riverbed (Bray et al., 2017; Neilson et al., 2010).…”
Section: Introductionmentioning
confidence: 99%